Estimating the harms and costs of cannabis-attributable collisions in the Canadian provinces. (1st April 2017) - Wettlaufer, Ashley; Florica, Roxana O.; Asbridge, Mark; Beirness, Douglas; Brubacher, Jeffrey; Callaghan, Russell; Fischer, Benedikt; Gmel, Gerrit; Imtiaz, Sameer; Mann, Robert E.; McKiernan, Anna; Rehm, Jürgen
Highlights: Cannabis collisions resulted in 75 deaths and 4407 injuries in 2012. There were up to 24, 879 victims of property damage only cannabis collisions in 2012. Cannabis collisions costs ranged from 1.09 to 1.28 billion CAD in 2012. Cannabis collision harms were particularly high amongst those ages 16–34 years old. Abstract: Introduction: In 2012, 10% of Canadians used cannabis and just under half of those who use cannabis were estimated to have driven under the influence of cannabis. Substantial evidence has accumulated to indicate that driving after cannabis use increases collision risk significantly; however, little is known about the extent and costs associated with cannabis-related traffic collisions. This study quantifies the costs of cannabis-related traffic collisions in the Canadian provinces. Methods: Province and age specific cannabis-attributable fractions (CAFs) were calculated for traffic collisions of varying severity. The CAFs were applied to traffic collision data in order to estimate the total number of persons involved in cannabis-attributable fatal, injury and property damage only collisions. Social cost values, based on willingness-to-pay and direct costs, were applied to estimate the costs associated with cannabis-related traffic collisions. The 95% confidence intervals were calculated using Monte Carlo methodology. Results: Cannabis-attributable traffic collisions were estimated to have caused 75 deaths (95% CI: 0–213), 4407 injuries (95% CI: 20–11, 549) and 7794 people (95% CI: 3107–13, 086) were involved in property damage only collisions in Canada in 2012, totalling 1, 094, 972, 062 (95% CI: 37, 069, 392–2, 934, 108, 175) with costs being highest among younger people. Discussion: The cannabis-attributable driving harms and costs are substantial. The harm and cost of cannabis-related collisions is an important factor to consider as Canada looks to legalize and regulate the sale of cannabis. This analysis provides evidence to help inform Canadian policy to reduce the human and economic costs of drug-impaired driving.